Estrogens Modulate Somatostatin Receptors Expression and Synergize With the Somatostatin Analog Pasireotide in Prostate Cells - Rossi, Valentina; Di Zazzo, Erika; Galasso, Giovanni; De Rosa, Caterina; Abbondanza, Ciro; Sinisi, Antonio A.; Altucci, Lucia; Migliaccio, Antimo; Castoria, Gabriella (Frontiers in Pharmacology, 2019)
Prostate cancer (PC) is one of the most frequently diagnosed cancers and a leading cause of cancer-related deaths in Western society. Current PC therapies prevalently target the functions of androgen receptor (AR) and may only be effective within short time periods, beyond which the majority of PC patients progress to castration-resistant PC (CRPC) and metastatic disease. The role of estradiol/estradiol receptor (ER) axis in prostate transformation and PC progression is well established. Further, considerable efforts have been made to investigate the mechanism by which somatostatin (SST) and somatostatin receptors (SSTRs) influence PC growth and progression. A number of therapeutic strategies, such as the combination of SST analogues with other drugs, show, indeed, strong promise. However, the effect of the combined treatment of SST analogues and estradiol on proliferation, epithelial mesenchyme transition (EMT) and migration of normal- and cancer-derived prostate cells has not been investigated so far. We now report that estradiol plays anti-proliferative and pro-apoptotic effect in non-transformed EPN prostate cells, which express both ERα and ERβ. A weak apoptotic effect is observed in transformed CPEC cells that only express low levels of ERβ. Estradiol increases, mainly through ERα activation, the expression of SSTRs in EPN, but not CPEC cells. As such, the hormone enhances the anti-proliferative effect of the SST analogue, pasireotide in EPN, but not CPEC cells. Estradiol does not induce EMT and the motility of EPN cells, while it promotes EMT and migration of CPEC cells. Addition of pasireotide does not significantly modify these responses. Altogether, our results suggest that pasireotide may be used, alone or in combination with other drugs, to limit the growth of prostate proliferative diseases, provided that both ER isoforms (α and β) are present. Further investigations are needed to better define the cross talk between estrogens and SSTRs as well as its role in PC.